An open design for a low-cost open-loop subsonic wind tunnel for aerodynamic measurement and characterization. (October 2022) - Ismail; Augupta Pane, Erlanda; Abdu Rahman, Reza
Graphical abstract: Abstract: A wind tunnel is an essential device for aerodynamic modeling and measurement. High cost and relatively huge size with no open market design hinder the wind tunnel from being widely available in laboratory design for universities and small R&D companies, particularly in a developed country with limited research funding. Thus, most aerodynamic modeling and measurement are done by simulating through computer software which leads to high deviation as the nature of wind is unpredictable. This project aims to provide an open design for a relatively low-cost wind tunnel that universities and R&D companies can quickly adapt. An open design for an open-loop wind tunnel is presented in this article. The proposed wind tunnel design is specifically intended to help the researcher with the aerodynamic measurement with minimum cost for building, customizable design, and reliable measurement. The components, parts, and equipment use the widely available part, which can be obtained across the globe. Validation and characterization are done using software simulation and actual measurement through the device. The proposed design can meet the criteria for aerodynamic measurement and can help the researcher provide a better analysis by combining the actual measurement and software simulation.